Analysing Students' Spatial Abilities in Chemistry Learning Using 3D Virtual Representation - Yuli Rahmawati; Hanhan Dianhar; Fadhillah Arifin (MDPI AG, 2021)
Students often have difficulty understanding abstract concepts in chemistry and a low spatial ability, especially in visualizing intermolecular interactions at the submicroscopic level. Therefore, this study aims to analyze the spatial ability of students by using a 3D virtual representation as they study the curriculum topic of molecular geometry. The research was conducted with 13 male and 23 female year 10 secondary students in Jakarta, Indonesia. A qualitative methodology was employed to analyze students' spatial abilities while they undertook learning activities using 3D virtual representation. Data collection included a spatial assessment, a quiz about prior knowledge, student worksheets, interviews, observation sheets, reflective journals, and a molecular geometry test. Learning was carried out in three stages; engage, explore, and explain. The results of the research show that students' ability in spatial orientation is low whereas their ability in spatial relationships that involve using mental manipulation and rotation of 2D or 3D objects is more developed. Students employ this approach to develop their understanding of molecular geometry.